Possibilities and limitations of electrospun chitosan‐coated polycaprolactone grafts for rotator cuff tear repair. (10th November 2019) - Willbold, Elmar; Wellmann, Mathias; Welke, Bastian; Angrisani, Nina; Gniesmer, Sarah; Kampmann, Andreas; Hoffmann, Andrea; de Cassan, Dominik; Menzel, Henning; Hoheisel, Anna Lena; Glasmacher, Birgit; Reifenrath, Janin
Abstract: Acute and chronic rotator cuff tears remain challenging for therapy. A wide range of therapeutic approaches were developed but re‐tears and postoperative complications occur regularly. Especially in elderly people, the natural regeneration processes are decelerated, and graft materials are often necessary to stabilize the tendon‐to‐bone attachment and to improve the healing process. We here investigated in a small animal model a newly developed electrospun polycaprolactone fiber implant coated with a chitosan‐polycaprolactone graft copolymer and compared these implants biomechanically and histologically with either a commercially available porous polyurethane implant (Biomerix 3D Scaffold) or suture‐fixed tendons. Fifty‐one rats were divided into three groups of 17 animals each. In the first surgery, the left infraspinatus tendons of all rats were detached, and the animals recovered for 4 weeks. In the second surgery, the tendons were fixed with suture material only (suture‐fixed group; n = 17), whereas in the two experimental groups, the tendons were fixed with suture material and the polyurethane implant (Biomerix scaffold group; n = 17) or the modified electrospun polycaprolactone fiber implant (CS‐g‐PCL scaffold group; n =17), respectively. The unaffected right infraspinatus tendons were used as native controls. After a recovery of 8 weeks, all animals were clinically inconspicuous. In 12 animals of each group, repaired entheses were biomechanically tested for force at failure, stiffness, and modulus of elasticity, and in five animals, repaired entheses were analyzed histologically. Biomechanically, all parameters did not differ statistically significant between both implant groups, and the entheses failed typically at the surgical site. However, with respect to the force at failure, the median values of the two implant groups were smaller than the median value of the suture‐fixed group. Histologically, the modified polycaprolactone fiber implant showed no acute inflammation processes, a good infiltration with cells, ingrowth of blood vessels and tendinous tissue, and a normal fibrous ensheathment. Further improvement of the implant material could be achieved by additional implementation of drug delivery systems. Therewith, the used CS‐g‐PCL fiber mat is a promising basic material to reach the goal of a clinically usable graft for rotator cuff tear repair.